The urgency of the androgenic screening for men who underwent preventive medical examination for prostate diseases detection - A. A. Kamalov; M. Ye. Chaly; R. P. Vasilevsky (Бюллетень сибирской медицины)
The bad influence of the androgenic insufficiency for men defines the need for obligatory androgenic screening of more than 50 years old patients. Testosterone level was examined. The criteria was the patients’ will to examine their status. The group consisted of 386 people from 20 to 87 years old (the average age is 58.7 years). It was found out that 160 people (41.45%) had age-related hypogonadism. Men’s androgenic deficit diacrisis algorithm was proposed for the ambulance situation.